2016
DOI: 10.5937/kgjsci1638053p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and expert system approach to photoionization theories

Abstract: ABSTRACT. The influence of the ponderomotive and the Stark shifts on the tunneling transition rate was observed, for non-relativistic linearly polarized laser field for alkali atoms, with three different theoretical models, the Keldysh theory, the Perelomov, Popov, Terent'ev (PPT) theory, and the Ammosov, Delone, Krainov (ADK) theory. We showed that aforementioned shifts affect the transition rate differently for different approaches. Finally, we presented a simple expert system for analysis of photoionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In our model we will assume that once the tensile stress exceeds a critical value σ c associated with the tensile strength of the ice, the brittle shell will crack open. Although the tensile strength of ice does not seem to be so widely investigated, values between 0.7 and 3.1 MPa have been reported [31]. The geometric amplification factor R o /∆R for thin shells may explain why in the initial stage liquid is easily squeezed out in the form of a spicule.…”
mentioning
confidence: 99%
“…In our model we will assume that once the tensile stress exceeds a critical value σ c associated with the tensile strength of the ice, the brittle shell will crack open. Although the tensile strength of ice does not seem to be so widely investigated, values between 0.7 and 3.1 MPa have been reported [31]. The geometric amplification factor R o /∆R for thin shells may explain why in the initial stage liquid is easily squeezed out in the form of a spicule.…”
mentioning
confidence: 99%
“…3C. These values are much higher than those reported in other forms of ice (e.g., <0.3%) (12,22,23), and the strain maxima measured at −150°C (>10%) are approaching the theoretical elastic limit (13,24). Even having experienced ultra-large strain, all the bent IMFs returned to their original shape, indicating the absence of the type of creep that ice Ih in other forms generally suffers from under high strain (23,28,29).…”
Section: Elastic Bending Of Imfsmentioning
confidence: 62%
“…As a result, ice has been extensively studied in the past centuries (1,2,(6)(7)(8)(9)(10). Bulk ice is rigid and fragile, leading to natural phenomena such as avalanches, glacier sliding, and sea ice fragmentation (1,11,12). The maximum elastic strain is experimentally found to be much lower than the theoretical limit of >10% (13).…”
mentioning
confidence: 99%
“…The compressive strength of solid ice increases by approximately fourfold when transitioning from 0 to −40 °C. [ 59 ] Freezing enabled us to prepare GelMA hydrogel‐based MNs with complete demolding and improved mechanical strength, and the addition of CPAs ensured acceptable cell survival. Consistent with our results, a previous study found that fabrication in medium containing 10% DMSO did not enable the production of morphologically intact cryoMNs.…”
Section: Discussionmentioning
confidence: 99%